1986
DOI: 10.1037/0735-7036.100.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Pavlovian conditioned approach behavior in male Japanese quail (Coturnix coturnix japonica).

Abstract: A localized visual stimulus presented immediately prior to access to a female conspecific stimulated approach behavior in male Japanese quail after several conditioning trials. Development of this conditioned approach behavior was observed with two different types of signal lights, 10-s and 30-s signal durations, large and small experimental chambers, and with male birds housed continually in the conditioning chambers or only placed in the chamber for brief daily sessions. Conditioning also resulted in shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 16 publications
(29 reference statements)
6
115
1
Order By: Relevance
“…17,18,22,[46][47][48] The control birds in which the view of the female was not paired with copulatory opportunity never developed this behavior. After approximately four training tests, the ASB and CSB birds were reliably expressing the learned response and were spending most of the test time in front of the window providing visual access to the female.…”
Section: Behavioral Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…17,18,22,[46][47][48] The control birds in which the view of the female was not paired with copulatory opportunity never developed this behavior. After approximately four training tests, the ASB and CSB birds were reliably expressing the learned response and were spending most of the test time in front of the window providing visual access to the female.…”
Section: Behavioral Resultsmentioning
confidence: 98%
“…In Japanese quail, appetitive sexual behavior (ASB) has been studied with the use of a variety of learning procedures developed by Domjan and his colleagues. [45][46][47] This behavior is testosterone-dependent, as demonstrated by the fact that low levels of circulating testosterone induced by exposing males to short photoperiods 39,76,83 or by surgical castration prevent the acquisition of the learned social proximity response commonly used to quantify ASB. 22,45 Moreover, males transferred from long days to short days will extinguish a previously acquired response.…”
mentioning
confidence: 99%
“…The typical outcome is that conditioned responding declines during the course of the extinction trials. In keeping with these f indings, early work with an arbitrary light CS showed that sexually conditioned approach behavior declined during a series of CS-alone extinction trials (Domjan et al, 1986). In a recent study, Krause, Cusato, and Domjan (2003) compared extinction with an arbitrary and a naturalistic CS.…”
Section: Resistance Of a Naturalistic Cs To Extinctionmentioning
confidence: 90%
“…In the first such study, Farris (1967) presented a buzzer to male quail just before giving them access to a sexually receptive female and found that the buzzer CS came to elicit courtship responses. Domjan, Lyons, North, and Bruell (1986) failed to replicate the conditioningof courtship behavior but found that males would approach and remain near an arbitrary visual CS (a light) that had been paired with sexual reinforcement. Subsequent research showed that this conditioned approach behavior is not disrupted by an omission contingency and is, therefore, not instrumentally mediated (Crawford & Domjan, 1993).…”
Section: Sexual Conditioning With Arbitrary Cssmentioning
confidence: 99%
See 1 more Smart Citation